The Impact of Executive Characteristics on Company Policy and Performance: The Case of London Stock Exchange Listed Companies (FTSE100) - Amara Tijani, Necib Adel (Mathematical Statistician and Engineering Applications, 2022)
This research aims to investigate the effect of managerial characteristics on firm policy and performance. This research uses data from UK-listed companies (FTSE100) during the period 2015 - 2021. The results show that female Chief Executive Officers have a negative impact on financing policy. It has a positive effect on company performance, but no significant effect on investment policy. We also find that Chef Executive Officer education has a negative effect on financing policy, but a positive effect on investment policy and performance. At the same time, Chief Executive Officer’s age has a negative influence on financing policy, but no influence on investment policy and performance. The results of our research support the theory of behavioral finance by providing empirical evidence that the behavioral aspects of the manager is been correlated with female gender, education, and age in terms of influencing firm policies and performance. The implication of this research is that investors should be aware of the characteristics of the Chief Executive Officer of the companies in which they invest their money because Chief Executive Officer Characteristics can be using as a benchmark for predicting performance and executive policy decision-making